Pengaruh Faktor Situasional terhadap Keputusan Pembelian Makanan di Pusat Perbelanjaan Tunjungan Plaza Surabaya - Ilham, . (Kajian Manajemen dan Bisnis, 2010)
The purpose of this study is to examine and analyze the influence of situational factors, namely buying intention; assortment; favorite stores; atmosphere; convenience; tour; quality and price; companion; travel time; staying time; frequency: number of stores visited; and satisfaction; that significantly affect consumer purchasing decisions of food products at the Tunjungan Plaza Surabaya shopping centre. This study uses primary data collected from questionnaires distributed to the respondents who are visitors of Tunjungan Plaza Surabaya. The sample consists of 150 respondents. The technique used in this study is logistic regression that is used to test the influence of situational factors on purchase decisions of food products. The results of this study indicate that six (6) factors from thirteen (13) existing situational factors affect consumers in purchasing decision of food products.